Comparison and optimization of three commercial methods with an LC–MS/MS method for the determination of sulfites in food and beverages. (15th July 2019) - Carlos, Katherine S.; Treblin, Mascha; de Jager, Lowri S.
Highlights: Four sulfite methods including rapid detections tests were evaluated for precision and accuracy. Ten commercially sulfited food products were evaluated in triplicate by each method. Correlation plots comparing the methods were prepared for evaluation and comparison of the methods. Abstract: Sulfites are food additives found in a large variety of food products to help reduce oxidation and browning. A small subset of the population has "allergic-like" symptoms upon consumption of sulfite containing foods. There are several sulfite detection methods available in the literature that vary in analysis time and required instrumentation. There are also rapid screening tests available that have not been tested extensively for accuracy and precision. In this study, four different methods (an LC–MS/MS method, a spectrophotometric method, a test strip method and a spot test method) were used to determine the sulfite concentration of 10 different commercially sulfited products. Of these methods, the LC–MS/MS and the spectrophotometric method had the most comparable results. The test strips were only accurate at concentrations greater than 50 mg/kg (ppm) SO2 . The spot test method was found to be inaccurate with both standard solutions and samples.